Changes of methylation at enhancers appear to be essential for HIV infection progression - Olga Taryma-Leśniak; Jan Bińkowski; Kaja Mielczak; Bogusz Aksak-Wąs; Malwina Karasińska-Cieślak; Marta Sobalska-Kwapis; Dominik Strapagiel; Miłosz Parczewski; Tomasz Kazimierz Wojdacz (Clinical Epigenetics)
Abstract Background We studied the influence of the European HIV-1 subtype B (most common in the Western and Central Europe) and subtype A6 (prevalent in Eastern Europe including Ukraine and Russia) on host methylome during infection progression and in virus-subtype-specific manner. Results Our results show that regardless of virus subtype, in the initial phase of the infection, HIV-related methylation changes more frequently affect parts of the genome with low expression activity including heterochromatin and quiescent regions. But, at stage four of the infection regions of the genome harboring HIV-related methylation changes are enhancers. We further showed that the effect of each of the virus subtypes on host methylome is to a large extent similar. And both virus subtypes appear to induce hypomethylation of loci associated with key pathways involved in viral infection such as ‘type I interferon signaling pathway,’ 'innate immune response' or 'negative regulation of viral genome replication.' Nevertheless, our results also indicate that each of the virus subtypes at least to some extent affects host methylome in virus-subtype-specific manner. Lastly, we showed that infection progression-related methylation changes that we identified are reversed with antiretroviral therapy. Conclusions We have shown that progression of HIV infection is associated with hypomethylation of enhancers regardless of virus subtype. This suggests that methylation changes at the enhancers may be key for infection progression. However, we also identified methylation changes indicating that, each of the virus subtypes affects host methylome in specific manner, but these findings need to be confirmed in studies that include larger number of participants.